Music for Martians: Schillinger's Two Tonics and Harmony of Fourths in Leigh Steven's Score for War of the Worlds (1953) - Rosar, William H. (Journal of Film Music, 2009)
After seeing Steven Spielberg’s remake of War of the Worlds on the 4th of July weekend 2005, an old friend who sat with me duringthe screening commented on how effective John Williams’ score for it was, and that it reminded her of film noir scores. An interesting coincidence, I thought, as many years earlier I had been struck by how passages in Leith Stevens’ score for Paramount’s War of the Worlds (1953) reminded me of “crime drama music,” music for gangster or detective movies. Why should Stevens and Williams write music for a science fiction film in a style evocative of another film genre?